A single‐center, open‐label positron emission tomography study to evaluate brivaracetam and levetiracetam synaptic vesicle glycoprotein 2A binding in healthy volunteers. (29th March 2019) - Finnema, Sjoerd J.; Rossano, Samantha; Naganawa, Mika; Henry, Shannan; Gao, Hong; Pracitto, Richard; Maguire, Ralph P.; Mercier, Joël; Kervyn, Sophie; Nicolas, Jean‐Marie; Klitgaard, Henrik; DeBruyn, Steven; et al.
Summary: Objective: Brivaracetam (BRV) and levetiracetam (LEV) are antiepileptic drugs that bind synaptic vesicle glycoprotein 2A (SV2A). In vitro and in vivo animal studies suggest faster brain penetration and SV2A occupancy (SO) after dosing with BRV than LEV. We evaluated human brain penetration and SO time course of BRV and LEV at therapeutically relevant doses using the SV2A positron emission tomography (PET) tracer 11 C‐UCB‐J (EP0074 ;NCT02602860 ). Methods: Healthy volunteers were recruited into three cohorts. Cohort 1 (n = 4) was examined with PET at baseline and during displacement after intravenous BRV (100 mg) or LEV (1500 mg). Cohort 2 (n = 5) was studied during displacement and 4 hours postdose (BRV 50‐200 mg or LEV 1500 mg). Cohort 3 (n = 4) was examined at baseline and steady state after 4 days of twice‐daily oral dosing of BRV (50‐100 mg) and 4 hours postdose of LEV (250‐600 mg). Half‐time of 11 C‐UCB‐J signal change was computed from displacement measurements. Half‐saturation concentrations ( IC 50 ) were determined from calculated SO. Results: Observed tracer displacement half‐times were 18 ± 6 minutes for BRV (100 mg, n = 4), 9.7 and 10.1 minutes for BRV (200 mg, n = 2), and 28 ± 6 minutes for LEV (1500 mg, n = 6). Estimated corrected half‐times were 8 minutes shorter. The SO was 66%‐70% for 100 mg intravenous BRV, 84%‐85% for 200 mg intravenous BRV, and 78%‐84% for intravenous 1500 mg LEV. The IC 50 of BRV (0.46 μg/mL) was 8.7‐fold lower than of LEV (4.02 μg/mL). BRV data fitted a single SO versus plasma concentration relationship. Steady state SO for 100 mg BRV was 86%‐87% (peak) and 76%‐82% (trough). Significance: BRV achieves high SO more rapidly than LEV when intravenously administered at therapeutic doses. Thus, BRV may have utility in treating acute seizures; further clinical studies are needed for confirmation.